Understanding guilt, shame and social service use in a diversity context - Nicole Syringa Harth; Diana Düring (Social Work and Society)
In Social Work, the differentiated handling of emotions is of great importance, especially in the complex web of relationships between clients and service providers. This paper presents an integrative approach to the exploration and regulation of emotions in the context of client-provider relationships. It highlights the crucial, but still understudied role that emotions play and draws on insights from different perspectives, to illustrate their role in understanding social experiences and guiding practical interventions. We will focus on the emotions of guilt and shame and their interplay with facets of diversity, especially racism and poverty. Shame is known as a feeling that results from the perception of not living up to social norms and expectations. Guilt is related to shame but is more based in the perception of having done wrong. Thus, one aim of this paper is to identify diversity-related patterns on the inter-personal and organizational level that increase the risk of shaming and guilt among clients, but also service providers. We will highlight the theoretical, empirical but also practical issues regarding these emotions and emphasize the importance of diversity and cultural sensitivity in client-provider relationships.